Developing of Chemically Treated Waste Biomass Adsorbent for Dye Removal. Issue 7 (3rd July 2021) - Asim, Nilofar; Amin, Mohamad Hassan; Alghoul, M. A.; Sulaiman, Siti Nur Ain; Razali, Halim; Akhtaruzzaman, M.; Amin, Nowshad; Sopian, Kamaruzzaman
ABSTRACT: In this study, different chemically treated coconut coir (CC), local waste biomass, has been developed as an adsorbent for the removal of methylene blue (MB) from an aqueous solution. The acid and base treated coconut coir with higher water and moisture absorbency have been investigated for dye removal performance. The influence of different experimental factors such as initial MB concentration and condition of chemical treatments on dye removal performance of coconut coir were studied. The compositional and structural changes of the treated samples were determined using X-ray diffraction (XRD), scanning electron microscope (SEM), X-Ray photoelectron spectroscopy (XPS), Fourier Transform Infrared spectroscopy (FT-IR), and Thermogravimetric analysis (TGA). The best sample showed the removal percentage of methylene blue equal to % 92.36 and %91.62 in 0.05mM and 0.03 mM of MB, respectively. The results showed the simply modified cheap waste biomass could be used as an effective green adsorbent for dye removal in aqueous solution.